2015
DOI: 10.1002/advs.201500250
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Hierarchical Nanostructure in Ternary Organic Solar Cells

Abstract: Ternary organic solar cells (OSCs), which blend two donors and fullerene derivatives with different absorption ranges, are a promising potential strategy for high‐power conversion efficiencies (PCEs). In this study, inverted ternary OSCs are fabricated by blending a highly crystalline small molecule BDT‐3T‐CNCOO in a low band gap polymer PBDTTT‐C‐T:PC71BM. As the small molecule is introduced, the overall PCEs increase from 7.60% to 8.58%. The morphologies of ternary blends are studied by combining transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
(82 reference statements)
0
42
0
1
Order By: Relevance
“…[9][10][11][12][13] Therefore, compared with the corresponding binary systems, TSCs have the potential to achieve higher light-harvesting and/or improved charge transport, leading to increased J sc and/or FF. [14][15][16] However, it should be noted that the emission of the third component and the absorption of the donor or acceptor must overlap in order to get efficient energy transfer. In addition, the morphology tuning highly depends on the crystallinity and miscibility properties of the materials involved.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Therefore, compared with the corresponding binary systems, TSCs have the potential to achieve higher light-harvesting and/or improved charge transport, leading to increased J sc and/or FF. [14][15][16] However, it should be noted that the emission of the third component and the absorption of the donor or acceptor must overlap in order to get efficient energy transfer. In addition, the morphology tuning highly depends on the crystallinity and miscibility properties of the materials involved.…”
mentioning
confidence: 99%
“…The resulting changes in film morphology, i.e., high crystallinity and appropriate phase separation, boosted the PCE from 6.85% to 8.40%. Similar phenomena were observed when BDT‐3T‐CNCOO was added to a PBDTTT‐C‐T:PC 70 BM blend: the domain size and purity are increased when 50% BDT‐3T‐CNCOO is incorporated; moreover, the presence of BDT‐3T‐CNCOO induces the formation of nanofibrous polymer domains that facilitate charge transport . Huang et al incorporated 2,4‐bis[4‐( N , N ‐diisobutylamino)‐2,6‐dihydroxyphenyl] squaraine (SQ) into a P3HT:PC 60 BM blend and found that it broadens the spectral absorption and induces the formation of a nanomorphology .…”
Section: Morphology Controlmentioning
confidence: 68%
“…Generally, a ternary blend has one additional electron donor or acceptor material compared with its binary counterpart. In addition to complementary absorption with respect to the binary blend, the third component also plays a very important role in tuning the morphology of the active layer though molecular interactions between the donors and acceptors, resulting in pure domains, face‐on orientations, and higher crystallinity, which are beneficial for exciton dissociation and charge transport . As a consequence, the J sc and FF are improved for ternary OSCs.…”
Section: Current Status Of Organic Solar Cellsmentioning
confidence: 99%